Evaluation Of Discrimination Index Of Single Best Response Type Of Multiple Choice Questions In Physiology By Item Analysis (Journal of Pharmaceutical Negative Results, 2023)
Introduction: The most reliable format of objective evaluation is multiple choice questions (MCQs) which ideally should be drawn from a question bank of valid and tested MCQs. Discrimination index is one of the most important tool to assess the quality and validity of a MCQ/Item. An item should be able to discriminate between those students with high tests scores and those with low ones. Higher the discrimination index of an item, better is the ability of the item to discriminate between students with high tests scores and those with low ones.Objectives: The objectives of the study were to find out discrimination index for each item in a physiology MCQ test paper.Materials and methods: Physiology MCQ test paper comprising of 40 items, with answer key and answer papers of 198 first MBBS students were obtained. Choice marked for each item by each student and his scores were entered in Microsoft Excel. Students were ranked & top 1/3rd and bottom 1/3rd were chosen as high achiever and low achiever group respectively. Discrimination index for each item was determined using appropriate formula.Results: 2 items had acceptable discrimination index, 13 items had good discrimination index,10 items had excellent discrimination index. 15 items had poor discrimination index out of which3 items had negative discrimination index.Conclusion: Valid items with discrimination index more than 0.2 can be incorporated in item bank. Items with discrimination index less than 0.2 should be either revised or discarded. Discrimination index can detect flaws in test questions and is helpful in giving appropriate feedback to teachers and students.